COMPARATIVE ANALYSIS OF MINERAL COMPOSITION IN PLANTS OF GENUS HEMEROCALLIS L. GROWING IN URBANIZED ENVIRONMENT - Pyatina , Irina Sergeevna; Reut , Antonina Anatolyevna; Afonkina , Svetlana Razifovna; Mryasova , Luiza Minibulatovna; Shakurova , Elvira Rifovna; Parfenova, Lyudmila Vyacheslavovna (Химия растительного сырья, 2025)
The quality and quantity of elements of the mineral composition of a plant directly affects the nature of the physiological effect on the human body, using this plant for food or as a medicine. The ability of plants to form the mineral composition in a certain way in an urbanized environment may be one of the reasons for the risk of using these plants for the human and animal organisms in view of their possible contamination with toxic substances. Ornamental flower plants of the genus Hemerocallis L. growing in Europe, North America, Russia and in the countries of Southeast Asia have been used in folk medicine since ancient times, and flowers and buds are eaten. The purpose of this study was to determine and compare the content of heavy metals in 14 taxon of the genus Hemerocallis L. The elemental composition of roots and leaves in dried plant raw materials, of the juice and the collection site soil was studied by atomic adsorption spectrometry. The order of decrease of the studied metals in underground and aboveground organs is established as follows: Cu˃Mn˃Ni˃Pb˃Fe˃Cr˃As˃Cd. It was noted that the average content of heavy metals Pb, Cd and Mn is higher in plant leaves. The average content of As, Cr, Fe, Cu and Ni prevailed in the roots of plants. Species- and variety-specific accumulation of heavy elements in the leaves and roots of the studied daylily taxon was noted.